EVOLUCION Y PROYECTOS DE LA ECONOMIA PERUANA - Roca, Santiago (1995)
This article analyzes the Peruvian economy’s evolution during 1994 and its prospects for the next two years. Concerning 1994, according to the main economic indicators, we find that the country grew for the second consecutive year and reduced its inflation level. This result was influenced by two factors: the increase of domestic interest rate in foreign currency’s and the considerable income from privatization. As for the projections for 1995-1996, it was found that inflation (7-8% annual growth) and economic growth (7% annual growth) would be manageable as long as the assumptions about public expenditure, privatization revenues, and capital flows during the period were met. However, these same elements threaten the exchange rate, a central problem for the medium-term economic program’s viability. Also of concern is the dependence on foreign savings and the low level of domestic savings. We conclude by pointing out that in the future it will be necessary to promote economic investment that generates employment and not only financial investment, as well as to significantly reduce the external debt.